Si Anak Emas Radin Jambat: A Legendary Tale from the Land of Lampung in Carousel Format - Rohiman, Rohiman; Prasetyo, Sigit Yudi; Selvia, Laela (Universitas Negeri Medan, 2025)
Local cultural implied folk tales have rich cultural and traditional values, but unfortunately they are less popular in Generation Z, who grew up in the digital era and have been exposed to global culture, but are usually more interested in modern and international content. They spend a lot of time in the digital world, especially social media. Therefore, social media can be used as an appropriate strategy to introduce folk/local wisdom to Generation Z. This study focuses on the design of illustrated stories that produce carousel-style folk tales/local wisdom on the Instagram platform. Data from this study were collected through observation, interviews, documentation and literary research. The design method involves five core phases: design thinking, including empathy, definition, idea, prototype and test. This study has shown an illustrated story,